Situs Arjuna Metapa Di Gianyar, Bali: Sebuah Patirthan? - Coleta Palupi Titasari; Rochtri Agung Bawono (Balai Arkeologi Sumatera Utara, 2015)
Every archaeological remain is always found in context with certain space and building architecture. This is also the case with the archaeological finds at the site of Arjuna Metapa at Pejeng Village in Gianyar, Bali. Uncovering a holy bathing place is the focus of this research, which is based on supporting data in form of archaeological data found within the location. The methods being used to solve the problem are divided into two: data collection and data analyses. Data collecting involves surface survey, bibliographical study, and interviews, while data analyses include qualitative-artifactual analysis, comparative and correlation analysis, location/spatial analysis, and physical traces analysis. Data obtained from research and analyses reveal that the Arjuna Metapa Site was a patirthan (holy bathing place) with water spouts, indicated by two spouted statues on Arjuna Metapa pedestal, which are meditating Arjuna spouted statue and angel spouted statue. Supporting data in form of an angel statue, which has similar form and size, was also found at the Village Temple (Pura Desa) of Bedulu. Oral tradition also mentions that the area was known by the name of Uma Telaga and is believed to be a rice field that was previously a lake or bathing place. This is confirmed by the discovery of Air Tiga inscription in that location. The name Air Tiga (air means water and tiga means three) is probably refer to the number of statues found in that location, which is one meditating Arjuna spouted statue and two angels spouted statues.